Level Of Study Of Happiness In Uzbek Psychology (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article spoke about the observation (in a unique aspect) of two conditions in the objective and subjective phenomenon of happiness, the connection of a person with living conditions, mental states, the perception of a person's psyche, life, his attitude to it, the complex of subjective experiences associated with their spiritual acceptance. In addition, research related to this topic has been shown that the study of the problem is still very relevant today.